Acute Systemic Response Of BDNF, Lactate and Cortisol to Strenuous Exercise Modalities in Healthy Untrained Women - García-Suárez, Patricia C. (Dose Response, 2020)
Acute bouts of intense exercise increase lactate concentration, which in turn stimulates brain-derived neurotrophic factor (BDNF) production. Cortisol released during intense exercise might inhibit BDNF synthesis. This study examined the acute effects of 2 protocols of strenuous exercise on serum BDNF. Seventeen physically-active healthy females (Age = 20.0 ± 0.9 yr., BMI = 23.0 ± 2.6 kg/m(2)) performed a strenuous cycle-ergometer graded exercise test (GXT) and a high-intensity interval training session (HIIT). Serum BDNF, serum cortisol, cortisol: BDNF ratio and blood lactate (BLa) were recorded at baseline and immediately following exercise. Although non-statistically significant, the HIIT session elicited a higher magnitude of change from baseline for BDNF (d = 0.17) and cortisol (d = 1.18) than after the GXT (d = -0.26, and d = 0.82, respectively). An interaction was found between GXT and HIIT trials and measurements on BLa levels, with higher post-exertion values after HIIT than after GXT (p < 0.0001, η(2) = 0.650, 95%CI = 2.2, 5.2). The higher BLa levels did not raise circulating BDNF. The elevated cortisol levels may have overcome the effects of lactate on BDNF. However, the higher BLa induced by HIIT suggest that interval exercise modality on the long-term could be a feasible intervention to increase circulating peripheral BDNF, at least in untrained healthy women.